The Social Impact Of River Pollution On The Community In Berok Nipah Village, West Padang District, Padang City - Mahfauza, Mahfauza; Fadilla, Annisa Nur; Zuriya, Rima; Irwan, Irwan (STABN RADEN WIJAYA WONOGIRI, 2025)
The pollution of the Batang Arau River in Berok Nipah Village, Padang Barat Subdistrict, Padang City, has caused various serious problems that directly impact the social life of the surrounding community. Pollution caused by domestic waste, traditional markets, and unprocessed industrial waste has led to a decline in water quality, sedimentation, and an increased risk of flooding. This study aims to uncover the social impacts of this pollution using qualitative methods with a constructivist approach. Data was collected through observation, in-depth interviews, and documentation. The analysis revealed that river pollution has led to an increase in water-related diseases, a decline in fishermen and farmers' incomes due to ecosystem damage, and limited access to clean water. Additionally, low public awareness and limited waste management facilities are major obstacles in addressing this issue. This study emphasizes the importance of collaboration between the government, community, and private sector in managing river environments sustainably to improve the quality of life for communities and prevent broader social impacts.